Peningkatan Keprofesionalan Guru oleh Kepala Sekolah Melalui Penelitian Tindakan Sekolah di SD Warisa Kecamatan Talawaan Kabupaten Minahasa Utara - Novita Sesiye Norma Kaunang (Peneliti.net, 2022)
SD Inpres Warisa is one of the schools located in Warisa Village, Talawaan District, North Minahasa Regency. The strategic position in improving the quality of education is held by professional teachers, because the implementation of quality learning is the spearhead. Therefore, the professionalism of teachers needs to be continuously improved, especially in terms of teaching students in the schools they lead. As managers and supervisors, principals have main duties related to empowering school resources, including teachers, along with their ongoing guidance. Through PTS, school principals can carry out their main substantive tasks as managers and supervisors in a more planned, methodological, systematic and accountable way. The performance of professional teachers in teaching can also be improved by the principal through PTS